UMA COMUNIDADE INVENTADA: CONFLUÊNCIAS DE SABERES DA ERER EM DIÁLOGO COM A ARTE - Lunelli, Diego (2024)
This report talks about the movement for creation of the Afro-Brazilian and Indigenous Studies Center Iaô and an overview of pedagogical work experiences towards implement the article 26-A from the Law of Guideline and Bases to the National Education, with perspectives from the Law 10.639/03 and 11.645/08, within the scope of Caxias do Sul Education Secretariat. We chose a path woven by movement, displacement and metaphors to build routes of collectivity. From the students’ production it was possible to establish one possibility of how pedagogical practices crossed by the Education in Ethnic and Racial Relations take place in the classroom, where it is possible to learn in community, recognize yourself  and the other. The results of the report points us to think about the reconstruction of a powerful anti-racist curriculum from the collectivity/community, to boost the ancestral knowledge of Indigenous and black people, without losing sight of the way we relate to school and mainly to our peers.